Keadilan Redistribusi Perspektif Islam - Bahrina Almas (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
The problem of poverty is the result of unequal distribution of income and wealth in the midst of society. The aspect of justice is very dominating why poverty can occur and how poverty can be overcome. Islam as a rahmatan lil 'alamin religion has provided practical solutions to prevent and alleviate poverty with the concept of redistribution. The purpose of this study is to find out how the concepts and instruments of redistribution in the Islamic perspective. This research is a literature study with content analysis. Data is collected through scientific literature, journals, articles and documents relating to research themes. The results show that redistribution in Islam has existed since the time of the Prophet Muhammad, since the formation of Madinah as a state, with zakat and tax as an instrument. Tithes and taxes do not recognize a fixed form but are still bound by intrinsic values ​​that aim at realizing socio-economic justice.